Someday our gods will be friends Journal for Religion, Film and Media - René Erwich (Journal for Religion, Film and Media, 2020)
This article reflects on the recent tv-series 'Vikings' from a practical-theological perspective. We deal with the series as a serious expression of the relationship between film and religion. The narrative, reception, style and context are used to present deliberate themes regarding clashes of pagan religion and Christianity. It is contended that the way a series like 'Vikings' has been developed and constructed, operates within the perspective of a liquefaction of religion.